Screening for sleep apnoea risk in testosterone-treated transgender men - Šnobrová, Bára; Burdová, Kristina; Weiss, Vladimír; Šonka, Karel; Weiss, Petr (Frontiers in Neurology, 2023)
Introduction Obstructive sleep apnoea (OSA) is more prevalent in men. Some studies suggested that higher testosterone levels were associated with a greater risk of OSA. We sought to determine whether testosterone administration in transgender men would accentuate symptoms of OSA. Methods The study involved 94 adult people undergoing a female-to-male transition with testosterone administration. The participants answered the Berlin questionnaire (BQ) and a separate question on snoring before starting testosterone treatment and after at least one year of being on testosterone treatment. Results The first category of BQ devoted to snoring was answered positively by more participants at the follow-up. The second category of BQ devoted to tiredness was answered positively by more participants at treatment entry. The percentage of subjects with a high risk of sleep apnoea, according to BQ, and subjects answering the question on snoring positively did not change significantly. Conclusions An increased number of transgender men who reported snoring in BQ after testosterone administration may indicate a higher risk of OSA development.